POLITICAL ECONOMY OF RUSSIA-UKRAINE WAR AND THE MACRO-ECONOMIC INSTABILITY IN EUROPE - CELESTINE OGECHUKWU OKAFOR; WOYINMO TIMI AMAKOROMO; VICTOR IHEANYI ASIEGBU (International Studies Journal)
The Russia-Ukraine war, stemming from a complex web of historical, geopolitical, and territorial disputes, has evolved into a multifaceted crisis with profound implications across political, economic, and humanitarian domains. This war originated with Russia's annexation of Crimea in 2014, followed by support for separatist movements in eastern Ukraine, challenging Ukraine's sovereignty and territorial integrity. This paper argued that the war reflects a broader geopolitical ambition, with Russia and Western countries aiming to assert influence in the region and maintain control over strategic territories. This has created a power struggle between Russia and Western nations, impacting the stability of Eastern Europe and beyond. Thus, we employed a time-series research design and documentary methods of data collection while relying on content analysis. The study adopted the Economic Incentive Theory of War as its theoretical framework. The findings of this paper showed that the war has far-reaching implications, notably impacting energy security in Europe due to disruptions in energy supply routes. Moreover, the imposition of sanctions on Russia by Western nations has led to economic repercussions not only for Russia but also for various European economies with interlinked trade relations. The study concluded that resolving the Russia-Ukraine war is pivotal not only for restoring peace and stability in the region but also for safeguarding global security and promoting sustainable economic development in Europe. Therefore, it was recommended that Ukraine maintain neutral status and not join military alliances perceived as threats by Russia while implementing the Minsk agreements.